2009
DOI: 10.1152/ajpheart.00705.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in myocardial infarct size at 48 hours after brief intravenous infusion of ATL-146e, a highly selective adenosine A2A receptor agonist

Abstract: Patel RA, Glover DK, Broisat A, Kabul HK, Ruiz M, Goodman NC, Kramer CM, Meerdink DJ, Linden J, Beller GA. Reduction in myocardial infarct size at 48 hours after brief intravenous infusion of ATL-146e, a highly selective adenosine A2A receptor agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The exact role of adenosine and its receptors in the setting of exercise-mediated cardioprotection needs to be further evaluated. It has been previously reported that stimulation of A 2a R early after MI attenuates inflammation (73) and preserves cardiac function and that prereperfusion stimulation reduces infarct size (58) and attenuates contractile dysfunction in the remote LV. Subsequently, increased A 2a R signaling due to pre-MI exercise could be associated with cardioprotective effects in the early remodeling stages and may have paved the way for further antifibrotic mechanisms in the progressive remodeling progress.…”
Section: Adenosine Receptors Are Upregulated By Exercise: a Potentialmentioning
confidence: 97%
“…The exact role of adenosine and its receptors in the setting of exercise-mediated cardioprotection needs to be further evaluated. It has been previously reported that stimulation of A 2a R early after MI attenuates inflammation (73) and preserves cardiac function and that prereperfusion stimulation reduces infarct size (58) and attenuates contractile dysfunction in the remote LV. Subsequently, increased A 2a R signaling due to pre-MI exercise could be associated with cardioprotective effects in the early remodeling stages and may have paved the way for further antifibrotic mechanisms in the progressive remodeling progress.…”
Section: Adenosine Receptors Are Upregulated By Exercise: a Potentialmentioning
confidence: 97%
“…Activation of A 1 and A 2A receptors has been shown to reduce ischemia-reperfusion injury in the heart (Schlack et al, 1993;Lozza et al, 1997). Brief intravenous infusion of ATL-146e, a selective adenosine A 2A receptor agonist (added 30 minutes before reperfusion), reduced myocardial infarct size at 48 hours after reperfusion after a period of ischemia (Patel et al, 2009). Selective A 3 receptor activation is cardioprotective in wild-type hearts and hearts overexpressing A 1 receptors.…”
Section: Ischemiamentioning
confidence: 99%
“…A brief intravenous infusion of ATL-146e, a selective adenosine A2AR agonist (added 30 min before reperfusion), reduced myocardial infarct size at 48 h after ischaemiareperfusion perturbation [547]. Endogenous adenosine is an important mediator of ischaemic preconditioning and postconditioning (see [548]).…”
Section: Ischaemiamentioning
confidence: 99%
“…Infarct size was reduced after a brief intravenous infusion of a selective A2AR agonist, ATL-146e [547]. In a clinical trial, a high dose of intracoronary adenosine given during percutaneous coronary intervention (PCI) did not reduce infarct size [638].…”
Section: Myocardial Infarctionmentioning
confidence: 99%